Perancangan Iklan Video Animasi sebagai Konten Media Promosi Produk “Kopi DungJes” dengan menggunakan Ibis Paint X, FlipaClip & Capcut - Susanto (Jurnal Sistem Informasi dan Teknologi Informasi, 2022)
If we look at the current era, the development of information technology is very rapid and has a big influence on various aspects of human life. One of them is the science of Multimedia, Multimedia Science is a media that combines two or more elements consisting of text, graphics, images, photos, and audio in an integrated manner which aims to convey information.Multimedia is widely used as a means for marketing a product/service. Advertising acts as a promotional medium for a product/service because it contains various content that is able to attract customers.By using animated videos, it has several added values ??for creators, one of which is that creators can freely process whatever is needed so that they can produce video advertisements in animation that are very interesting and contain a message in it, so that they can become a special attraction.In making animated video promotions made using the Ibis Paint X application as a drawing tool, FlipaClip as a tool to unite images to become moving images and Capcut as an editor to unite audio and video to make it a promotional advertisement with the theme of 2D animation video.